Optimización del desempeño energético para el transporte de hidrocarburos en el oleoducto de los Llanos Orientales mediante la utilización del agente reductor de fricción extreme power (2021)
The present work shows through a simulation under laboratory conditions the use of a friction reducing agent at different concentrations (1000 ppm, 1700 ppm, 1900 ppm, 2300ppm) which reduces the energy consumption required to transport crude oil in the Pipeline of the Eastern Plains. For this process, an evaluation of the characteristics of the crude oil transported through flow tests was carried out, varying the proposed concentrations in order to find the best concentration that would reduce the viscosity of the crude oil transported, relieving the work of the pumps used, and reducing the energy consumption of these. Additionally, a computational simulation was performed using the Aspen HYSYS software that allowed evaluating the behavior and friction losses of the different concentrations proposed along the Oleoducto de los Llanos. It was found that the concentration No.4 (2300 ppm) significantly reduces the viscosity of the crude oil in the flow tests carried out and also obtains the smallest values ​​of friction losses obtained in the computational simulation. Finally, a financial analysis of the project was carried out taking into account the results obtained from the flow tests and the computational simulation for each proposed concentration through the indicator Net Present Value (NPV) and Internal Rate of Return (IRR), choosing the concentration financially more attractive for the company.